Reuse of cells in mead production using Tamarindus indica pulp as an unconventional supplement - Silva, Anne Kettery Carneiro e; Anunciação, Adriana Soares; Canettieri, Eliana Vieira; Bispo, José Ailton Conceição; Martínez, Ernesto Acosta (Springer Nature, 2022)
In classic fermentations, the costs related to the additional consumption of raw materials and the longer fermentation times related to the inoculum propagation stage can be reduced through the reuse of yeast. This study aims to evaluate the production of mead with the reuse of two Saccharomyces cerevisiae strains (AWRI 796 and Montrachet) supplemented with tamarind pulp in four consecutive fermentation batches. The must (30°Brix) was fermented without or with 30% tamarind pulp and inoculated with 106 cells/mL in 500 mL Erlenmeyer flasks at 30 °C for 284 h. The addition of tamarind pulp decreased the volumetric productivity, the substrate to ethanol conversion factor and the efficiency of the fermentation process. S. cerevisiae Montrachet showed higher values of volumetric productivity in ethanol even in the presence of tamarind pulp as an unconventional supplement in the fermented must. The reuse of cells in consecutive fermentation batches to produce mead contributed to the reduction of initial costs of inoculum growth, and fermentation time.
Keywords: Honey; Mead; Recycling of yeast; Saccharomyces cerevisiae; Tamarind